2011
DOI: 10.1093/nar/gkr954
|View full text |Cite
|
Sign up to set email alerts
|

WormBase 2012: more genomes, more data, new website

Abstract: Since its release in 2000, WormBase (http://www.wormbase.org) has grown from a small resource focusing on a single species and serving a dedicated research community, to one now spanning 15 species essential to the broader biomedical and agricultural research fields. To enhance the rate of curation, we have automated the identification of key data in the scientific literature and use similar methodology for data extraction. To ease access to the data, we are collaborating with journals to link entities in rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
192
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(196 citation statements)
references
References 37 publications
(39 reference statements)
4
192
0
Order By: Relevance
“…gff2, downloaded from WormBase (Yook et al 2012), which annotates 2390 repeat elements in the studied region. Repeats are classed into 594 categories, which include several types of simple sequence repeats and low-complexity tracts (e.g., TTTA n , polypyrimadine, A rich, etc.…”
Section: Annotation Analysismentioning
confidence: 99%
“…gff2, downloaded from WormBase (Yook et al 2012), which annotates 2390 repeat elements in the studied region. Repeats are classed into 594 categories, which include several types of simple sequence repeats and low-complexity tracts (e.g., TTTA n , polypyrimadine, A rich, etc.…”
Section: Annotation Analysismentioning
confidence: 99%
“…Orthologs of C. elegans genes were identified using either the Homologene database at the National Center for Biotechnology Information or the Panther database from within WormBase (Mi et al 2010;Sayers et al 2012;Yook et al 2012). RNAi was performed largely as described previously (Alper et al 2008).…”
Section: Use Of Rnai In Mouse Macrophages To Test Candidate Genesmentioning
confidence: 99%
“…Experiments were performed at 20°C unless noted. The genes and alleles in this work are described in Wormbase (www.wormbase.org) (Harris et al, 2010;Yook et al, 2012) unless otherwise indicated.…”
Section: Strains and Allelesmentioning
confidence: 99%